(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
In this article, the main goal of the modern education system is the transition to the dynamic development of innovation and the qualitative growth of human capital, the strategy of our educational policy. Therefore, the introduction of rapidly developing educational technologies in the field of education requires the professionalism of teachers and readiness to master new information technologies. The main purpose of this is to change, access, analyze and present, and communicate information to students and teachers. It is envisaged that the use of electronic resources in the educational process in educational organizations can contribute to both the development of professional skills and the use of experience in using the environment.